Quantum theory of the Vavilov-Cherenkov radiation for a particle with arbitrary spin - Afanasiev, G.N.; Lyubchenko, M.V.; Stepanovsky, Yu.P. (Вопросы атомной науки и техники, 2007)
We consider the Vavilov-Cherenkov radiation by a particle with arbitrary spin using the relativistic quantum treatment of the one-photon Cherenkov emission. The probability of the one-photon emission by relativistic particle is calculated in the framework of quantum electrodynamics using the covariant parameterization of electromagnetic current for particle with arbitrary spin. Розглянуте випромінювання Вавілова-Черенкова частинкою з довільним спіном. Iмовірність випромінювання одного фотона релятивістською частинкою обчислена в рамках квантової електродинаміки з використанням коваріантної параметризації матричних елементів електромагнітного струму частинки з довільним спіном. Рассмотрено излучение Вавилова-Черенкова частицей с произвольным спином. Вероятность излучения одного фотона релятивистской частицей рассчитана в рамках квантовой электродинамики с использованием ковариантной параметризации матричных элементов электромагнитного тока частицы с произвольным спином.